THE ROLE OF CLUB OF ROME IN FORMING THE CONCEPT OF SUSTAINABLE DEVELOPMENT - Божко, С. В. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2021)
Global problems and crises are the actual reality of our time. Their prevention, solution and reduction of their impact concerns not only the existing generation, but also the future one, due to the fact that everyone should have equal opportunities and rights to access resources. Considering the pace of development of various spheres, we see that humanity tends to deplete resources, so the idea arose to solve these problems by coordinated actions of the global community. These ideas underlie the Concept of Sustainable Development, which today is supported and implemented, especially by many states of the world. But these ideas developed even before the concept was created, in particular, within the framework of the activities of the Club of Rome. The purpose of this article is to reveal how the activities of the Club of Rome influenced the process of formation and development of the concept of sustainable development. Аor this, the methods of theoretical generalization, analysis and synthesis of information were used. The activities of the Club of Rome began thanks to Aurelio Peccei (author of «Human Qualities»), who created a non-governmental organization that became world famous for a series of reports on the pressing and global problems of humankind. In particular, the 1972 study «The Limits to Growth» by D. and D. Meadows, who described models of the world in the future and a number of recommendations on how to avoid a catastrophic development of events. The publication had great resonance and was heavily criticized, but started a world-class discussion. In particular, the Club of Rome was involved in the discussion at the UN. So, the active work of the non-governmental organization Club of Rome not only started discussions about the global crisis, but also provided a solid theoretical and empirical basis for the development of the Concept of sustainable development. Club members took an active part in the development of sustainable development at a more local level in their regions. Thus, the organization has achieved its primary goal — to attract attention to the global problems and create an action plan to resolve them.